Computer education : literacy and beyond - Schall, William E.; Leake, Lowell Jr.;Whitaker, Donald R. (California : Brooks/Cole Publishing Company, 1986)
This book is intended primarily for perspective and in-service teachers, in all disciplines and at all grade levels, as well as for school administrators.
Chapter 1. Meet the computer -- Chapter 2. Fundamentals of basic programming -- Chapter 3. Control structures in basic -- Chapter 4. Nested loops and arrays in basic -- Chapter 5. Applications of basic -- Chapter 6. Logo - a second language -- Chapter 7. Pascal - a third language -- Chapter 8. A brief history of computers -- Chapter 9. Computers in the school -- Chapter 10. Computers in the home -- Chapter 11. The computer in business, science, and society -- Chapter 12. Dilemmas, differing views, and the future -- Chapter 13. Keeping up-to-date.
Includes index.
Keywords: COMPUTERS